Pengaruh Pengalaman Kerja dan Kemampuan Kerja Terhadap Kinerja Karyawan di Badan Keuangan dan Aset Daerah Kabupaten Malang - Wisik Aulia Jannah; Muhammad Ridwan Basalamah; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The role of employees is a driving factor for company goals. So that various companies strive to create optimal employee performance. With analysis factors that can encourage optimal employee performance, namely work experience and work ability. The purpose of this study was to find out the effect of work experience and work ability on employee performance in the Badan Keuangan dan Aset Daerah Kabupaten Malang. The population in this study were all employees at Badan Keuangan dan Aset Daerah Kabupaten Malang. In this study, we take the number of samples using Slovin's formula and get the calculation results with 64 respondents. Data were analyzed using multiple linear regression tests. The results of the study show that simultaneously and partially work experience and work ability have a significant effect on employee performance in the Badan Keuangan dan Aset Daerah Kabupaten Malang. Keywords: Work experience, Work ability, and Performance